Utilizing Digital Parenting Apps for Modern Parenting Practices and Child Protection: The Potential of BabyCenter and Google Family Link among Parents of Young Children - Angelina Kurnia Juita; Prisko Yanuarius Djawaria Pare; Abdul Halim Bin Masnan; Mallevi Agustin Nigrum; Eustakia Mogi (Smart Society, 2026)
The increasing use of digital technology in family life has transformed the way parents access parenting information and support, including in Malanuza and Bajawa, Ngada Regency. Various digital parenting apps are available to help parents obtain parenting information while supporting child protection in the digital environment. However, research on the potential use of digital parenting apps in supporting modern parenting and early childhood protection remains limited. This study aims to analyze the potential use of digital parenting apps, specifically BabyCenter and Google Family Link, in modern parenting practices and early childhood protection. The study employed a descriptive qualitative approach involving 10 young parents with young children who own smartphones. Participants were selected through purposive sampling to explore their perceptions regarding the usefulness, ease of use, and potential applications of both apps. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the Miles, Huberman, and Saldana model. The results indicate that BabyCenter is viewed as a potential source of information on child growth and development, health, nutrition, and managing sleep patterns, as well as parenting strategies appropriate for the child’s developmental stage. Meanwhile, Google Family Link is perceived as a tool that can help parents monitor their children’s digital activities, set device usage limits, and control access to inappropriate content. These findings suggest that both apps have the potential to support parenting practices while strengthening child protection in the digital environment. The uniqueness of this study lies in its examination of the potential for using BabyCenter and Google Family Link together to support modern parenting and early childhood protection, based on perceptions of usefulness and ease of use within the framework of the Technology Acceptance Model (TAM).